If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + 30) = 90 Reorder the terms: 6(30 + x) = 90 (30 * 6 + x * 6) = 90 (180 + 6x) = 90 Solving 180 + 6x = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-180' to each side of the equation. 180 + -180 + 6x = 90 + -180 Combine like terms: 180 + -180 = 0 0 + 6x = 90 + -180 6x = 90 + -180 Combine like terms: 90 + -180 = -90 6x = -90 Divide each side by '6'. x = -15 Simplifying x = -15
| 8z-6=58 | | 5z+5=40 | | .2x+.6y=.52*80 | | 25=X+X+6 | | 1.5(x-4)=9.2 | | Y=3/4(x-3/4) | | Y=x(x+20) | | 3a^3/4-2a^3/4 | | 3y+2y+y+9x= | | 2n^2+4n-16=0 | | (3x-4)(-7x+4)=0 | | 2/(3-i) | | -4+4x=-8+10 | | -3(s+3)+10=8 | | 3x-18=y | | 3x+11=12-x | | x^2+8.4x-40=0 | | 2x+x+x+y+y= | | x^2-12x+36=13 | | 48-a=4-a+7 | | 2x-14+6x-9+3x+2=180 | | 6x^5-5=43 | | −2/3-7/8w=9/4 | | 2(3x+5)=8x-8 | | 180-55=x | | 57+x+68=180 | | 5r-6=31 | | X^2+ax+100=0 | | 90-34=x | | 4r-6=31 | | -1/6=-8/21y | | 68+48+x=180 |